PENGARUH WORK LIFE BALANCE TERHADAP LOYALITAS KARYAWAN PADA GENERASI Z DI KOTA BANDUNG - Marsela, Gita; Puteri Andika Sari (Journal of Innovation Research and Knowledge, 2024)
The aim of this study is to determine the impact of work-life balance (X) on loyalty (Y) among Generation Z employees in Bandung. Generation Z tends to prioritize the balance of their personal and work lives. Generation Z is characterized by a lack of loyalty towards their work or company. The banking sector is one of the institutions that Generation Z is interested in. The method used in this research is to distribute questionnaires to 125 respondents and then process them using SPSS 29 with the analysis techniques of classical assumption tests, simple linear analysis, correlation coefficients, coefficients of determination, and hypothesis testing using the T test (partial). The results showed that work-life balance had an effect on increasing the employee loyalty variable by 35.2%; the remaining 67.5% was influenced by other variables or factors. Work-life balance has a positive and significant effect on employee loyalty; it is recommended that further research increase the number of respondents and distribute questionnaires with a wider scope to increase the accuracy of the research results